Non-Performing Financing in Indonesian Islamic Commercial Banks During the Pandemic: A Macro and Microeconomics Perspective - Riska Dewi; Abdul Hakim (Jurnal REKSA: Rekayasa Keuangan, Syariah dan Audit, 2022)
Non-performing financing (NPF) as a measure of the soundness of Islamic banks might face adverse reactions during the Covid-19 pandemic. This study aimed to determine the effect of macroeconomic variables, including inflation, BI rate, exchange rate, and microeconomic variables such as CAR, FDR, and BOPO on the NPF of Islamic Commercial Banks registered by the Indonesian Financial Services Authority for the period 2013:5 to 2021:6. It also aimed to investigate the effect of the covid-19 pandemic on the NPF. This study utilized the autoregressive distributed lag (ARDL) analysis method. The ARDL was used to analyze the relationship between NPF and the macro and microeconomics variables in the short and long term. The analysis results showed that the covid-19 pandemic, inflation, and BI rate significantly affected the NPF of the Indonesian Islamic commercial banks in the short and long term. Additionally, it was evidenced that BOPO was only significant in affecting the NPF in the short time, and FDR was only significant in determining the NPF in the long term.